The experience of living with diabetes mellitus - Percis P Khumalo; Mirriam Sebego; Cynthia Z Vilakati; Mildred SP Mkhabela; Tengetile R Mathunjwa-Dlamini (Archives of Community Medicine and Public Health - Peertechz Publications, 2021)
Diabetes mellitus is one of the chronic complex diseases which affect the physiological, social and psychological aspects of life, interfering with the functional health status of clients. As a chronic disorder, diabetes mellitus is a lifelong condition. The purpose of the study was to explore experiences of people living with type 2 diabetes mellitus at the Mbabane Government Hospital, Swaziland. The study utilized a qualitative exploratory design. Purposive sampling was used to select the participants. The sample size of 12 participants was determined by data saturation. A thematic data analysis was used. The themes that emerged were physiological, psychological; socio-economic and self-management effects of living with diabetes mellitus. The study findings call for empowerment of people suffering from diabetes mellitus with knowledge and skills on self-management, prevention and early detection of complications.